Pemanfaatan Buku Digital Pada Aplikasi iPusnas Dalam Meningkatkan Minat Baca di Kota Samarinda - Ridha, Muhammad; Kusasi, Muhammad (El-Idare, 2024)
The development of Information and Communication Technology (ICT) has transformed the paradigm of traditional libraries into more open and accessible digital libraries. iPusnas, a digital library application developed by the National Library of Indonesia (Perpustakaan Nasional Republik Indonesia, Perpusnas RI) in collaboration with the vendor Aksamaraya, is an example of innovation in utilizing ICT to enhance literacy access in Indonesia. This application offers various features such as book search, digital book borrowing, and offline reading capabilities, allowing users flexible access to thousands of book collections. This research reviews the development process of iPusnas, including concept design, software development, testing, and launch phases. The research methodology employed is a qualitative descriptive approach combining literature review, direct observation, and semi-structured interviews. The analysis results indicate that iPusnas significantly contributes to increasing reading interest in Samarinda City. Easy and quick access to various types of digital books, including contemporary and classic titles, provides a broader range of choices for the community to access readings according to their interests. Features such as efficient search, bookmarking, and interactive reading also enhance user engagement in literacy activities.